68Ga–Prostate-Specific Membrane Antigen Solitary Base of Skull Prostate Adenocarcinoma Metastasis. (January 2021) - Yip, Joshua Wei Liang; Hilliar, Luke; Le, Ken; Loh, Han; Mansberg, Robert
Abstract : Abstract: A 74-year-old man with prostate adenocarcinoma (Gleason 7) was referred for 68 Ga–prostate-specific membrane antigen (PSMA-HBED-CC) PET/CT scan for staging. Findings confirmed the prostate malignancy and demonstrated a solitary metastasis in the left skull base, with no evidence of regional or distant metastasis elsewhere. Solitary base of the skull metastasis may be subtle and easily overlooked, highlighting the need for thorough evaluation of the region.